Technology for the formation of competence in the protection and defense of intellectual property rights of graduates of pedagogical institution of higher education - Kulakovskyi, O. (Problems of Engineer-Pedagogical Education, 2021)
There is discussed and provided theoretical grounds for the development of the competence of graduates of higher educational establishments in the protection and defense of intellectual property rights in this article, the uniqueness of its realization is proved. The stages of the pedagogical technology of forming the competence of future teachers, namely: preparatory-diagnostic, motivational-target, cognitive-indicative procedural activity, monitoring and evaluation, are analyzed. The main components of each stage of the proposed pedagogical technology are examined, and the problems that need to be addressed in the training of future teachers in intellectual property are identified. The use of the results of the evaluation of the information obtained at the diagnostic stage has been found to be the basis for the development of a curriculum that will develop competence in the field of protection and defense of intellectual property rights, as well as the selection of teaching tools and methods. The significance, goals and objectives of the motivational-target stage of technology for achieving the required result are justified. An introduction of the discipline “Fundamentals of intellectual property in pedagogical activity” to the variable part of the curriculum is proposed, a thematic plan of the indicated discipline is developed. The possibility of including topics to the disciplines is considered on the example of CPP 011 Educational pedagogical sciences of the first (bachelor's) level, the compulsory component of which includes the discipline Educational innovations. Suggested topics for each module. Besides this, it is justified to include in the list of disciplines at the student’s choice course «Protection of intellectual property rights of teachers», or additional special course «International mechanisms of intellectual property rights protection». The author offers examples of classes that can be used to develop competence in the field of protection and defence of intellectual property rights. Some aspects of the construction of the factor-criterion model for carrying out the control-evaluation stage of the technology of forming the said competence of students have been considered. The algorithm of realization of the technology of formation competences in sphere of protection and defence of IP rights of future teachers is presented.